Stanje in notranja razmerja v slovenskem naprednem (liberalnem) taboru na pragu 2. svetovne vojne - Oskar Mulej (Dileme, 2023)
The article provides an outline of the development of the internal relations and divisions in the Slovenian progressive (liberal) camp in the years just before the Second World War and upon its start. After falling from power in 1935, the progressive camp was weak and internally fragmented. At the same time, the range of groups and ideological orientations found under the “progressive” umbrella was extremely wide as it extended far to the left and right sides of the political spectrum. The youth, in particular, were distinctly ideologically differentiated and radicalised. Some of them were highly susceptible to radical political approaches and moved towards fascism and communism. Especially when viewing the wider ideological camp, it is thus partly justified to posit a process of disintegration. At the same time, at least the core part maintained a consciousness of belonging to a common political camp, which was reflected by renewed connections between parties and groups on the eve of the war.